A 2020 Vision for food, agriculture, and the environment in Sub-Saharan Africa: a synthesis - Badiane, Ousmane; Delgado, Christopher L. (International Food Policy Research Institute, 1995)
The workshop participants were clear that now is the time for choices, and that without the will to make those choices, the likelihood of success in boosting agricultural growth on a sustained basis would be small. Without such growth, it will not be possible to improve food security or halt natural resource degradation. It seems unlikely that all countries of Africa will choose to put in place the necessary conditions for growth, which makes it all the more important to decide at the outset which conditions are most likely to beget further success. Participants highlighted four principal conditions that are interrelated: greater stability, probity, consistency, and analytical quality in the policymaking process for agriculture; increased public investment by national governments to facilitate growth in the agriculture sector; proactive adaptation to changing global trade conditions; and inclusion of the poor and malnourished in growth.